The Serotonergic System as a Target for Neuroendocrine Disruption in the Brain of Goldfish (Carassius auratus) - Mennigen, Jan A. (Université d'Ottawa / University of Ottawa, 2011)
Serotonin stimulates reproduction and inhibits feeding/growth in the neuroendocrine brain of goldfish. The objective of this thesis is to study the effects of selective serotonin reuptake inhibitor pharmaceuticals (SSRIs) on these systems, as SSRIs, such as fluoxetine, are detected in effluent and bioconcentrate in the brain of wild fish. Genes of the serotonin system were cloned to identify molecular conservation, seasonal expression, and tissue distribution. The serotonin transporter, the target molecule of fluoxetine, was highly conserved and ubiquitously expressed in goldfish. Seasonal changes of hypothalamic gene expression of the serotonin transporter support a role in the seasonal modulation of both processes. Fluoxetine injection experiments were used to assess effects on reproductive endpoints and to identify molecular mechanisms in the neuroendocrine brain. Fluoxetine inhibited serum estradiol concentrations in female goldfish and decreased isotocin mRNA abundance in the hypothalamus and telencephalon. Isotocin injections stimulated circulating estradiol concentrations, providing a causal link. Evidence for an involvement of serotonin in isotocin regulation was investigated using immunocytochemistry and 5-HT1A receptor agonists and antagonists. A close proximity of serotonin fibers and isotocin cell bodies and fibers was found in the telencephalon and pituitary,respectively. Injection of a 5-HT1A receptor antagonist inhibited isotocin mRNA expression in the telencephalon. Identified gene targets were investigated in waterborne fluoxetine exposures,including environmental concentrations. Waterborne fluoxetine led to a reduction in basal and pheromone-stimulated milt volume in male goldfish. Gene expression evidence indicated a central inhibitory effect of fluoxetine through the decrease in mRNA abundance of follicle-stimulating hormone in the pituitary and isotocin in the telencephalon. Feeding rate and weight decreased in fluoxetine-injected goldfish, indicating an anorexigenic effect. Fluoxetine induced changes in the gene expression of the feeding peptides neuropeptide Y, corticotropin-releasing factor, and cocaine- and amphetamine-regulated transcript-I in the hypothalamus and telencephalon. Waterborne exposure to fluoxetine validated the anorexigenic effect in goldfish and was correlated with increased expression of corticotropin-releasing factor mRNA, an anorectic peptide. The thesis provides evidence for disrupting effects of fluoxetine on neuroendocrine control of reproductive function and feeding/growth in goldfish, partially at environmental concentrations. The thesis provides the framework for the investigation of existing aquatic contaminants which modulate the serotonin system.
Keywords: neuroendocrinology; goldfish; serotonin; reproduction; SSRI; pharmaceutical; aquatic toxicology; growth; feeding; pharmaceutical